Redescription of Isotomiella alulu and I. delamarei (Collembola: Isotomidae) with notes on the systematics of the genus and new records from the Neotropics - Kovac, Ľubomír; Palacios-Vargas, Jose G. (Zootaxa, 2008)
Isotomiella alulu Christiansen & Bellinger, 1992 and I. delamarei Barra, 1968 are redescribed after the study of type material and comparison with related species in differential diagnosis. The systematic position of I. delamarei is specified with discussions of the systematics of the genus based on sensillar patterns of the species representatives. Two phyletic lineages are outlined within the genus represented by I. minor and I. nummulifer species groups. Diagnostic tables for Isotomiella species based on sensillar patterns and morphological characters of furcula are involved and a dichotomous identification key to the genus is provided. Notes on the systematics and distribution of Isotomiella species are added. New localities for I. granulata, I. nummulifer and I. symetrimucronata from the Neotropics (Mexico, Nicaragua) are given , and records of I. minor are confirmed for Northern and Central Mexico (Nearctic region).